Subcutaneous metastases from early stage esophageal adenocarcinoma case report. (2016) - Datta, Sujata; Muñoz-Largacha, Juan A.; Li, Lei; Zhao, Grace (Qing); Litle, Virginia R.
Highlights: Subcutaneous metastases from esophageal adenocarcinoma are rare. Associated risk factors have not been clearly elucidated and prognosis is poor. We present three cases of subcutaneous metastases from esophageal adenocarcinoma. These metastases can occur even after resection of early stage disease. They can occur at various intervals of time and various locations. Abstract: The identification of subcutaneous metastatic lesions from primary visceral malignancies has increased over time, probably due to an increase in the awareness of their presentation and an increase in cancer survival times. Although the rate of subcutaneous metastases from breast, lung and colon cancer is more significant, the incidence of subcutaneous metastases from esophageal carcinomas is very low. These metastatic lesions usually present metachronously and may signify advanced disease and poor prognosis. We report three cases with early stage esophageal adenocarcinoma treated with surgery with curative intent presenting with subcutaneous metastases two months, two years and three years after their esophagectomy.